Mengoptimalkan Kinerja Karyawan Melalui Lingkungan Kerja, Komitmen Organisasi dan Motivasi Kerja - Nafiah, Almaratu Sholihatun; Sutianingsih, Sutianingsih (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The investigation was conducted at the Purwodadi Branch of PT. Bina Arta Ventura. Performance is a dependent variable, while the work environment, organizational commitment, and employee motivation are independent variables. The primary objective of this investigation is to investigate and evaluate the impact of motivation, organizational commitment, and the work environment on employee performance. The sampling technique is saturated employing a census, as the sample of this study consists of 35 employees who are all employees. Multiple linear regression is implemented by the analysis instrument. In summary, the performance of employees at the PT. Bina Arta Ventura Purwodadi Branch is significantly and positively impacted by work environment factors, organizational commitment, and work motivation. Keywords: employee performance, organizational commitment, work environment, motivation